1975
DOI: 10.1039/p19750001531
|View full text |Cite
|
Sign up to set email alerts
|

Opium alkaloids. Part XVI. The biosynthesis of 1-benzylisoquinolines in Papaver somniferum. Preferred and secondary pathways; stereochemical aspects

Abstract: Tetrahydropapaverhe (VI), derived from (-)-nor-reticuline ( 11) and (-)-nororientaline (111), is the principal immediate precursor of papaverine ( V I I I ) in Papaver somniferum. The trimethyl ethers of papaveroline ( X I a ) and b) are incorporated less effectively into papaverine, the dimethyl ether ( X I c ) not a t all. Norprotosinomenine ( I V ) and noriso-orientaline(V) can also be biotransformed into papaverine in the plant, but this occurs by an aberrant route which does not involve tetrahydropapaveri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

1978
1978
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 0 publications
1
23
0
Order By: Relevance
“…The intermediate is ( S )-tetrahydropapaverine, a compound first postulated in papaverine biosynthesis (Brochmann-Hanssen et al, 1971) after it had been found as a natural product isolated from P. somniferum . This postulate was verified by Brochmann-Hanssen et al (1975) who synthesized (−)-tetrahydropapaverine that was found to be incorporated into papaverine with an, at that time, extremely high incorporation rate in the poppy plant. However, the opinion was that ( S )-norreticuline and norlaudanosoline are the precursors of norlaudanine, norlaudanosine, with the biosynthetic grid ending with tetrahydropapaverine and papaverine (Battersby, 1963; Brochmann-Hanssen et al, 1971; Uprety et al, 1975) but, as mentioned before, Brochmann-Hanssen and associates never found norreticuline, norlaudanine or norlaudanosine.…”
Section: Resultsmentioning
confidence: 75%
See 3 more Smart Citations
“…The intermediate is ( S )-tetrahydropapaverine, a compound first postulated in papaverine biosynthesis (Brochmann-Hanssen et al, 1971) after it had been found as a natural product isolated from P. somniferum . This postulate was verified by Brochmann-Hanssen et al (1975) who synthesized (−)-tetrahydropapaverine that was found to be incorporated into papaverine with an, at that time, extremely high incorporation rate in the poppy plant. However, the opinion was that ( S )-norreticuline and norlaudanosoline are the precursors of norlaudanine, norlaudanosine, with the biosynthetic grid ending with tetrahydropapaverine and papaverine (Battersby, 1963; Brochmann-Hanssen et al, 1971; Uprety et al, 1975) but, as mentioned before, Brochmann-Hanssen and associates never found norreticuline, norlaudanine or norlaudanosine.…”
Section: Resultsmentioning
confidence: 75%
“…This hypothetical intermediate was seemingly verified when it was shown that the expected labeled precursors were incorporated into papaverine, the target compound (Battersby and Harper, 1959,1962; Battersby et al, 1964), despite some discrepancies in the labeling patterns (for review see Spenser, 1969) produced in poppy and other isoquinoline alkaloid accumulating plants. Extensive phytochemistry, precursor synthesis and experimentation by Brochmann-Hanssen and associates (Brochmann-Hanssen and Furuya, 1964; Brochmann-Hanssen et al, 1965; Brochmann-Hanssen et al, 1971; Brochmann-Hanssen et al, 1975) not only discovered the now recognized true precursors of papaverine, the opium poppy-derived laudanine (laudanidine) and laudanosine alkaloids, but found in labeled ( S )-tetrahydropapaverine an excellent precursor for papaverine while ( R )-tetrahydropapaverine is largely inactive. However, ( R,S )-reticuline was very poorly incorporated into papaverine, but most importantly the highest incorporation rates into papaverine were achieved with norreticuline, which is missing the N -methyl group.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1). The efficient incorporation of radiolabeled N-desmethyl compounds (Brochmann-Hanssen et al 1975;Uprety et al 1975) and the identification of a norreticuline 7-O-methyltransferase (N7OMT), which accepts only norreticuline yielding norlaudanine (Pienkny et al 2009), provides biochemical support for the N-desmethyl pathway. A recent study using mass spectrometry and heavy stable-isotope labeling of (S)-reticuline, (S)-laudanine and (S)-laudanosine suggested that N-methylated 1-benzylisoquinolines are incorporated into papaverine at low levels (Han et al 2010), providing some support for the N-methyl pathway.…”
Section: Biosynthesis Of the Major Alkaloids In Opium Poppymentioning
confidence: 99%